(untitled) (Saptagandaki Journal, 2023)
This study aims to analyze teaching-learning activities through games from phenomenological perspectives. Phenomenological study focuses on understanding and meaning-making of students’ and teachers’ lived experiences collected through in-depth interviews, follow-up interviews, and observations. Regarding this, students learn best when they enjoy teaching learning activities. In games and/or game-like activities, students are stimulated to participate and work with heartfelt efforts. This study also focuses on learners’ participation in games or game-like teaching-learning activities and how they are empowered to face challenges and try their best to achieve the goal. The paper explores which games and game-like activities are practiced in community schools and what benefits and challenges the activities pose in the sense-making of teachers’ and students’ experiences. Participants were purposively selected from conveniently chosen schools. The study has also found that students enjoy learning from games and want to play them again and again. However, teachers, though they sometimes use games and game-like activities in class, do so only for refreshment and experimentation, not as part of actual teaching. Moreover, such teaching has no significant role in assessment. Finally, it concludes that students learn more and better from games or game-like activities than from existing traditional teacher-centered teaching. This study suggests that the concerned authorities should encourage teachers to develop and implement game-based activities and assess students’ learning achievements from them.